SUSTAINABLE TOURISM DEVELOPMENT IN THE GLOBAL ECONOMY - Nazarova, Khulkar (University Research Base, 2025)
Sustainable tourism is one of the important areas of the modern global economy and is based on the principles of environmental protection, local economy development and cultural heritage preservation. The article analyzes the impact of sustainable tourism on the global economy using the examples of France, Italy, Switzerland and Greece. These countries are achieving tourism sector development through sustainable infrastructure, ecotourism, green technologies and tourism management. The article discusses the main areas of sustainable tourism development and its positive impact on the global economy. The results show that sustainable tourism can bring long-term economic benefits and help preserve natural and cultural resources.